Switching to Faricimab for Polypoidal Choroidal Vasculopathy with Real-World Outcomes in Refractory Cases – The FAR-PEARL Study Report 1 - Fong KC; Wong WJJ; Wong HS; Ling KP; Fong SN; Shunmugam M (Clinical Ophthalmology)
Kenneth CS Fong,1 Wilson Jun Jie Wong,1 Hon Seng Wong,1 Kiet Phang Ling,1 Shir-Ning Fong,2 Manoharan Shunmugam1 1OasisEye Specialists, Kuala Lumpur, Kuala Lumpur, Malaysia; 2University of Nottingham Medical School, Nottingham, NG72UH, UKCorrespondence: Kenneth CS Fong, Email Ken.fong@oasiseye.myPurpose: To present real-world outcomes of switching to faricimab in eyes with polypoidal choroidal vasculopathy (PCV) refractory to previous anti-VEGF treatments.Methods: This retrospective study included PCV eyes switched to faricimab for recurrent PCV (> 180 days from prior anti-VEGF treatment), suboptimal extension (60– 180 days), or recalcitrant PCV (< 60 days). Patients were followed monthly, with PRN reinjections for persistent subretinal fluid (SRF), intraretinal fluid (IRF), or pigment epithelial detachment (PED) at the fovea, or a 1-line vision drop. The primary outcome was time to injection-free status (no injection for 3 months), analyzed via survival analysis.Results: We included 49 eyes with PCV (mean age 66.1 ± 9.5 years; 59% women), 29% had recurrent PCV, 37% suboptimal extension, and 34% recalcitrant disease. Patients had a median of 8 prior anti-VEGF injections,the majority being aflibercept and received a median of 3 faricimab injections (Interquartile range (IQR)=2-4, range=1-8)) over 344 days (IQR=198-446). The interval between the first two faricimab injections averaged 64 ± 43 days, longer in recurrent (86 ± 55 days) vs recalcitrant PCV (43 ± 26 days, p=0.008). By day 90, 49% were injection-free, increasing to 73% by day 210. PED resolved in 53% after the first dose, and in those needing repeat injections, the interval peaked after the fourth dose with no SRF, IRF, nor PED.Conclusion: The differential response to faricimab in PCV depends on disease type, with recurrent cases requiring fewer injections and recalcitrant cases requiring more intensive initial treatment; however, even recalcitrant eyes can achieve extended intervals after initial doses.Keywords: polypoidal choroidal vasculopathy, faricimab, refractory neovascular AMD, anti-VEGF resistance, visual and anatomical outcomes, real-world study